Investigation of Magneto-Convection Characteristics in A Sudden Expanding Channel with Convex Surface Geometry Under Thermally Developing Flow Conditions - Gursoy, Emrehan; Pazarlioglu, Hayati Kadir; Gurdal, Mehmet; Gedik, Engin; Arslan, Kamil; Dagdeviren, Abdullah (Research Square Platform LLC, 2023)
Abstract
The current study presents a novelty with focusing on the magnetic field effect on a sudden expansion tube with expansion ratio, total length, and pitch length of the dimpled fin is 2.5, 1500 mm, and 3.0, respectively. The magnetizable Fe3O4/H2O Ferrofluid with different nanoparticle volumetric concentrations (φ = 1.0% and 2.0%) were used as a heat transfer fluid, and magnetohydrodynamic effects were elaborately investigated in this study. The numerical analysis was conducted under laminar flow regime and the DC magnetic field (B0 = 0.03T, 0.05T, 0.3T, and 0.5T). The present study provided a comprehensive investigation, which presented the thermo-hydraulic performance of difference dimpled fins, Fe3O4/H2O Ferrofluid, and magnetic field. According to the results, dimple fins showed the best increment within heat transfer enhancement techniques. The heat transfer enhancement rate of the dimple tube and Fe3O4/H2O Ferrofluid were respectively acquired as 22.62% and 5.43%-6.28% (φ = 1.0% and 2.0%). When dimpled fin and Fe3O4/H2O Ferrofluid were used, the increment in Performance Evaluation Criteria was calculated as 21.31% and 4.85%-9.79% (φ = 1.0% and 2.0%). Although the highest average Nusselt number was obtained at B0 = 0.5T, the highest performance evaluation criteria were detected at B0 = 0.3T due to the friction factor showing an increment.